Hybrid harvesting strategies to overcome resource constraints: evidence from social enterprises in Kenya - Ciambotti, Giacomo (Journal of business ethics, 2021)
Hybrid organisations combine different elements from the for-profit and non-profit domains, and they usually operate in a resource-scarce environment. For these reasons, they continuously face various resources constraints, yet their hybrid nature could be translated into an opportunity. The purpose of our study was to investigate how a hybrid organisation can overcome resource constraints in developing countries by exploiting their own hybrid nature. In the unique research setting offered by Kenyan social enterprises, we identified five creative approaches implemented by social enterprises. Finally, we present a grounded model that clearly explains which hybrid harvesting strategies can be implemented to overcome resource constraints, exploiting their hybrid potential. Our work contributes to knowledge about resource constraints in the social entrepreneurship literature and extends social bricolage theory. Limitations and future research approaches are also presented.